2018
DOI: 10.1016/j.pedneo.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary artery hypertension in childhood: The transforming growth factor-β superfamily-related genes

Abstract: Pulmonary artery hypertension (PAH) is very rare in childhood, and it can be divided into heritable, idiopathic drug- and toxin-induced and other disease (connective tissue disease, human immunodeficiency virus infection, portal hypertension, congenital heart disease, or schistosomiasis)-associated types. PAH could not be interpreted solely by pathophysiological theories. The impact of the transforming growth factor-β superfamily-related genes on the development of PAH in children remains to be clarified. Pert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 55 publications
(66 reference statements)
0
11
0
1
Order By: Relevance
“…Besides, mutations, environmental changes and acquired adjustment of transforming growth factor (TGF)-β superfamilyrelated genes may explain at least partly the mechanisms of congenital PAH [12][13][14]. In these studies, it was revealed that an imbalance of vascular cellular proliferation, driven by stimulation of excessive growth factors, such as TGF-β family signaling, platelet derived growth factor (PDGF) and Notch receptor play an important role in the development of PAH [15]. It has been noted that, in the developmental course of PAH, the immune cells initiate and maintain inflammatory responses to infections [16,17], and to hypoxic insults of the lung [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, mutations, environmental changes and acquired adjustment of transforming growth factor (TGF)-β superfamilyrelated genes may explain at least partly the mechanisms of congenital PAH [12][13][14]. In these studies, it was revealed that an imbalance of vascular cellular proliferation, driven by stimulation of excessive growth factors, such as TGF-β family signaling, platelet derived growth factor (PDGF) and Notch receptor play an important role in the development of PAH [15]. It has been noted that, in the developmental course of PAH, the immune cells initiate and maintain inflammatory responses to infections [16,17], and to hypoxic insults of the lung [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that the inflammatory cytokine IL-6 might contribute to PAH in COPD and that IL-6 gene polymorphism endorses susceptibility to patients with PAH secondary to COPD. BMPR2 gene mutation might boost cell division and prevent cell death, leading to pulmonary vascular remodeling, and one-fifth of individuals with a BMPR2 gene mutation might progress into PAH [36]. Thus, BMPR2 gene mutations constitute the background of the pathogenesis of heritable PAH [37].…”
Section: Discussionmentioning
confidence: 99%
“…Isolated CHD lesions associated with NODAL mutations include D-TGA, double outlet right ventricle (DORV), TOF, and isolated VSDs. Overexpression of TGF-β1 seems to play a role in the development of pulmonary hypertension in patients with CHD, suggesting that alterations in this pathway may have pleo- tropic effects on the heart as well as the pulmonary vasculature (Gao et al 2005;Yuan 2018).…”
Section: Cell Signaling and Adhesion Modelsmentioning
confidence: 99%